Identities in Fur Trade Societies and Along the Colonial Frontier in Eastern Canada: A Case Study from Western Quebec - Inksetter, Leila; Morneau, Jérôme; Rousseau, Louis-Pascal (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2025)
Research in the field of Métis studies has focused on contexts where mixed-ancestry communities emerged, but much less on contexts where such entities did not materialize. The Upper Ottawa River, in western Quebec, represents a salient example of the latter. Despite the area’s prolonged involvement with the fur trade and the well-documented establishment of unions between European winterers and local First Nations women, the children born through these relationships did not coalesce into a separate mixed-ancestry community. This article examines the context of the fur trade in the area, the marital patterns that can be observed through nineteenth-century documentation, and the social outcomes available to the offspring born through these unions. It then attempts a comparison with other areas in the heart of the continent that acted as trade hubs. It concludes that most children born from mixed unions were integrated into First Nations communities and that no mixed-ancestry community emerged within the research area because the few mixed-ancestry families that were present lacked the critical mass to differentiate themselves from other social contexts.